Germline POLE and POLD1 proofreading domain mutations in endometrial carcinoma from Middle Eastern region - Siraj, Abdul K. (Cancer Cell Int, 2019)
BACKGROUND: Endometrial carcinoma (EC) accounts for 5.8% of all cancers in Saudi females. Although most ECs are sporadic, 2–5% tend to be familial, being associated with Lynch syndrome and Cowden syndrome. In this study, we attempted to uncover the frequency, spectrum and phenotype of germline mutations in the proofreading domain of POLE and POLD1 genes in a large cohort of ECs from Middle Eastern region. METHODS: We performed Capture sequencing and Sanger sequencing to screen for proofreading domains of POLE and POLD1 genes in 432 EC cases, followed by evaluation of protein expression using immunohistochemistry. Variant interpretation was performed using PolyPhen-2, MutationAssessor, SIFT, CADD and Mutation Taster. RESULTS: In our cohort, four mutations (0.93%) were identified in 432 EC cases, two each in POLE and POLD1 proofreading domains. Furthermore, low expression of POLE and POLD1 was noted in 41.1% (170/1414) and 59.9% (251/419) of cases, respectively. Both the cases harboring POLE mutation showed high nuclear expression of POLE protein, whereas, of the two POLD1 mutant cases, one case showed high expression and another case showed low expression of POLD1 protein. CONCLUSIONS: Our study shows that germline mutations in POLE and POLD1 proofreading region are a rare cause of EC in Middle Eastern population. However, it is still feasible to screen multiple cancer related genes in EC patients from Middle Eastern region using multigene panels including POLE and POLD1.